Moving Beyond the Keypress: As Technology Advances, so Should Psychology Response Time Measurements. (June 2021) - Kramer, Michelle R.; Cox, Patrick H.; Yu, Alfred B.; Kravitz, Dwight J.; Mitroff, Stephen R.
Decades of research in cognitive psychology have largely relied on simple key or button presses to quantify human behavior. While many valuable discoveries have been made, a richer response modality may reveal more information regarding the different processes that underlie complex human behavior. This study provides a proof of concept for using a touch-and-swipe response method to separate response time into two components to extract more meaningful behavioral insights. Across several analyses, the two components were consistently shown to be separable, independent measurements of behavior. Furthermore, evaluating these isolated response time components improved inferential power and clarity of behavioral patterns. The touch-and-swipe response method is simple and easy-to-use, and it shows promise for more accurately targeting mechanisms of interest.